Impact of nutritional diet therapy on premenstrual syndrome - Siminiuc, Rodica; Ţurcanu, Dinu (Frontiers in Nutrition, 2023)
Abstract. Premenstrual syndrome (PMS) is one of the most common disorders faced by women of reproductive age. More than 200 symptoms of varying severity associated with PMS have been identified. Because of the broad spectrum of action of PMS and its impact on quality of life, symptom relief is the main challenge of treating PMS and Premenstrual Dysphoric Disorder (PMDD). The review aims to analyze and identify the potential impact of dietary and nutritional therapies on PMS and, respectively, for its better management. The study was conducted by accessing Internet databases such as PubMed, ScienceDirect, and Scopus and using relevant keywords such as premenstrual syndrome, symptoms, dietary patterns, macro and micronutrients, and supplements. The results showed that diet is an essential modulating factor in reducing and managing PMS symptoms. But research on the actual effect of foods and nutrients on PMS is sparse, sporadic, and studied with insufficient scientific rigor. No correlations were identified between the consumption of macronutrients and PMS: protein, fat, carbohydrates, and fiber, but the effectiveness of micronutrients, especially calcium, magnesium, vitamin D, B vitamins, and herbal supplements, was demonstrated. Researchers remain unanimous that the evidence is insufficient and limited to support their use as an effective treatment. Nevertheless, the results could contribute to providing quality information to help women and girls make evidence-based decisions regarding premenstrual health and the adoption of dietary and nutritional therapies.